Architecture of software system for hierarchical fuzzy inference - Yershov, S.V.; Ponomarenko, R.М.. (PROBLEMS IN PROGRAMMING, 2018)
A software architecture for hierarchical fuzzy logic hierarchy based on fuzzy logic algorithmic models and separate parallel computing technologies such as MPI and CUDA has been developed, as well as key architectural design solutions to provide the flexibility and performance of a parallel fuzzy system. The patterns of designing and programming of different levels of abstraction, as well as the main software modules and interfaces of the fuzzy software system are analyzed. The method of containerization of applications for the GPU for their reuse and deployment on the selected software platform of high-performance parallel computing is presented.Problems in programming 2018; 2-3: 099-0108